ИССЛЕДОВАНИЕ RLC-ЦЕПИ СИНУСОИДАЛЬНОГО НАПРЯЖЕНИЯ С УПРАВЛЯЕМЫМ РЕВЕРСИРОВАНИЕМ ИНДУКТИВНОГО ЭЛЕМЕНТА - Шидловская, Н.А. (Інститут електродинаміки НАН України, Київ, 2011)
Upon reversing of inductive element the sin-voltage RLC-circuit processes due to controlled commutator were analyzed. Obtained recurrent formulae enable to determine the capacity voltage and the inductive current at any temporal intervals irrespective of numbers of reversals had been using the before in symmetric and asymmetric or reversing controls. Basic operating mode of RLC-circuit (oscillatory, limit, aperiodic) are researched. For circuits with different Q-factor and relations of interval sizes after even and odd reversing the capacity voltage and inductive current plots are shown. References 4, figures 5.